2013
DOI: 10.1002/etc.2116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of major cations (Ca2+, Mg2+, Na+, K+) and anions (SO, Cl, NO) on Ni accumulation and toxicity in aquatic plant (Lemna minor L.): Implications For Ni risk assessment

Abstract: Abstract-The effect of major cation activity (Ca 2þ , Mg 2þ , Na þ , K þ ) on Ni toxicity, with dose expressed as exposure (total dissolved Ni concentration Ni Tot ) or free Ni ion activity (in solution Ni 2þ ), or as tissue residue (Ni concentration in plant tissue Ni Tiss ) to the aquatic plant Lemna minor L. was examined. In addition, Ni accumulation kinetics was explored to provide mechanistic insight into current approaches of toxicity modeling, such as the tissue residue approach and the biotic ligand mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The phytotoxicity effects of elevated concentrations of soil Ni on maize seedlings include reductions in growth and the appearance of leaf spotting and chlorosis. This agrees with earlier reports on Ni toxicity responses, describing inhibited growth and leaf lesions [ 13 , 4 , 27 ]. Amari et al .…”
Section: Discussionsupporting
confidence: 93%
“…The phytotoxicity effects of elevated concentrations of soil Ni on maize seedlings include reductions in growth and the appearance of leaf spotting and chlorosis. This agrees with earlier reports on Ni toxicity responses, describing inhibited growth and leaf lesions [ 13 , 4 , 27 ]. Amari et al .…”
Section: Discussionsupporting
confidence: 93%
“…In some cases, these relationships may have been confounded by other covarying water quality parameters such as alkalinity and pH because of the specific ionic composition of natural and synthetic waters, but subsequent ion-specific studies have confirmed that increasing ambient Ca 2þ reduces both acute and chronic Ni toxicity to a variety of aquatic and terrestrial animals [3,[19][20][21][22][23][24]. In contrast, most studies indicate that Ca 2þ has no effect on Ni toxicity to aquatic or terrestrial plants, suggesting that Ni uptake occurs via different mechanisms in plants [25][26][27][28][29]. This may be related to Ni being an essential cofactor in plant ureases and hydrogenases [30].…”
Section: Disruption Of Ca 2þ Homeostasismentioning
confidence: 99%
“…Detailed explanations of the toxicity testing protocol have been published previously (Gopalapillai et al 2012(Gopalapillai et al , 2013. Briefly, the standardized Environment Canada protocol (EC 2007c) was followed with minimal changes.…”
Section: Methodsmentioning
confidence: 99%